The epidemiology of osteoporotic fractures - Harvey, N; Arden, N (2003)
Osteoporosis is a major public health issue affecting a large proportion of the population aged over fifty years. It leads to a huge burden through the increased morbidity and mortality associated with fragility fractures. Although the age-specific incidence of fractures has been increasing over the last 40 years in the West, this now seems to be plateauing. However, with the predicted increase in the world population, particularly the over 65's, over the next 40 years, the future burden of fractures will increase substantially. There is a large genetic component to peak bone mass, which is polygenic in origin. Increasingly it is recognised that environmental factors not only affect the rate of bone loss, but also affect peak bone mass gained. This has led to a new approach, based on the idea of "foetal programming". Patient assessment has, in the past, been based on bone mineral density and the relative risk of fracture. New approaches involve determining a patient's 5-10 year absolute risk of fracture, which will allow better targeting of today's more effective but expensive treatments.